Penyuluhan Konsumsi Ikan Pada Ibu Dan Anak Dalam Pencegahan Stunting di Desa Makrampai Kecamatan Tebas - Ridwan; Agam, Beryaldi; Merdekawati, Dewi; Yunita, Nurul Fatimah; Saputra, Iwan; Fitriyandi; Tantilia, Erma; Saputra, Ari; Bulano, Lassram; Winarto, Trijuli; Syafiq, Muhammad (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
Stunting is one of the conditions where children experience chronic nutritional problems. Counseling activities on the importance of fish consumption in mothers and children as an effort to prevent stunting were held on Tuesday, November 15, 2022 in Sutera Hamlet, RT 09 RW 04, Makrampai Village, Tebas District, Sambas Regency. The targets in counseling activities are mothers and children. Makrampai village is one of the villages that experiences quite high stunting. This counseling activity aims to increase knowledge and understanding of good nutrition, especially the importance of eating fish in mothers and children as an effort to prevent stunting. The counseling activities went well and smoothly. Participants consisting of mothers and children who participated in the counseling activity were very active and enthusiastic, Participants had an understanding of the importance of consuming fish to fulfill body nutrition and one of the efforts to prevent stunting.